2021
DOI: 10.3389/fneur.2021.683275
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Enzymes Involved in One-Carbon Metabolism and Anti-epileptic Drug Monotherapy on Homocysteine Metabolism in Patients With Epilepsy

Abstract: Aims: To investigate the effects of single nucleotide polymorphisms (SNPs) in genes of one-carbon metabolism (OCM) related enzymes and anti-epileptic drug (AED) monotherapy on homocysteine (Hcy) metabolism in patients with epilepsy, and to further explore specific SNPs that may increase patients' susceptibility to the effects of AEDs on the Hcy imbalance.Method: This case-control study analyzed 279 patients with epilepsy, including patients receiving monotherapy with valproate (VPA) (n = 53), oxcarbazepine (OX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The authors did not demonstrate genotype distributions. However, in the study, the MTHFR TT genotype was observed to increase patients' susceptibility to the effect of oxcarbazepine in disrupting homocysteine homeostasis [33].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The authors did not demonstrate genotype distributions. However, in the study, the MTHFR TT genotype was observed to increase patients' susceptibility to the effect of oxcarbazepine in disrupting homocysteine homeostasis [33].…”
Section: Discussionmentioning
confidence: 70%
“…Vurucu et al [32] demonstrated that 677C>T polymorphism of the MTHFR gene had no impact on elevated levels of homocysteine in epileptic children receiving carbamazepine or valproic acid. In addition, a recent study by Zhu et al [33] analyzed MTHFR polymorphism in epileptic patients and controls aged 15-55 years old but in reference to its impact on homocysteine levels. The authors did not demonstrate genotype distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Independent risk factors for elevated Hcy levels in patients with epilepsy were found to influence the Hcy homeostasis 5 . Furthermore, it has been documented that epilepsy and related disorders may occur as a result of gene polymorphism in 5,10methylenetetrahydrofolate reductase (MTHFR), along with the deficiency of vitamin B-12 (methylcobalamin), folic acid, and vitamin B6 (pyridoxal phosphate) 5 .…”
Section: Introductionmentioning
confidence: 96%
“…Some of the major causes are a head injury, brain infections like meningitis or encephalitis, brain tumors, birth defects, stroke, and even altered levels of blood components like sodium or blood sugar. Homocysteine (Hcy), a non-proteinogenic α-amino acid that is produced during methionine metabolism, is one blood component that may elevate in concentration mainly due to the deficiency of folic acid and/or vitamin B-12 leading to various risks [3][4][5] . Independent risk factors for elevated Hcy levels in patients with epilepsy were found to influence the Hcy homeostasis 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation